Continuous Magnesium Sulfate Infusions for Status Asthmaticus in Children: A Systematic Review - Johnson, Peter N.; Drury, Anna Sahlstrom; Gupta, Neha (Frontiers in Pediatrics, 2022)
OBJECTIVES: Magnesium sulfate is a second-tier therapy for asthma exacerbations in children; guidelines recommend a single-dose to improve pulmonary function and decrease the odds of admission to the in-patient setting. However, many clinicians utilize prolonged magnesium sulfate infusions for children with refractory asthma. The purpose of this review is to describe the efficacy and safety of magnesium sulfate infusions administered over >1 hour in children with status asthmaticus. METHODS: Medline was searched using the keywords “magnesium sulfate” and “children”. Articles evaluating the use of magnesium sulfate infusions >1 hour published between 1946-August 2021 were included. Published abstracts were not included because of lack of essential details. All articles were screened by two reviewers. RESULTS: Eight reports including 447 children were included. The magnesium regimens evaluated included magnesium delivered over 1 hour (n=148; 33.1%), over 4-5 hours (n=105; 23.5%), and over >24 hours (n=194; 43.4%). Majority of patients received a bolus dose of 25-75 mg/kg/dose prior to initiation of a prolonged infusion (n=299; 66.9%). For the patients receiving magnesium infusions over 4-5 hours, the dosing regimen varied between 40-50 mg/kg/h. For those receiving magnesium infusions >24 hours, the dosing varied between 18.4-25 mg/kg/h for a duration between 53.4-177.5 hours. Only three reports including 186 patients (41.6%) included an evaluation of clinical outcomes including evaluation of lung function parameters, reduction in PICU transfers, and/or decrease in emergency department length of stay. Five reports including 261 patients (58.4%) evaluated magnesium serum concentrations. In most reports, the goal concentrations were between 4-6 mg/dL. Only 3 (1.1%) out of the 261 patients had supratherapeutic magnesium concentrations. The only reports finding adverse events attributed to magnesium were noted in those receiving infusions >24 hours. Clinically significant adverse events included hypotension (n=74; 16.6%), nausea/vomiting (n=35; 7.8%), mild muscle weakness (n=22; 4.9%), flushing (n=10; 2.2%), and sedation (n=2; 0.4%). CONCLUSIONS: Significant variability was noted in magnesium dosing regimens, with most children receiving magnesium infusions >4 hours. Most reports did not assess clinical outcomes. Until future research is conducted, the use of prolonged magnesium sulfate infusions should be reserved for refractory asthma therapy.